Laparotomic Myomectomy in the 16th Week of Pregnancy: A Case Report - Lavinia Domenici; Violante Di Donato; Maria Luisa Gasparri; Francesca Lecce; Jlenia Caccetta; Pierluigi Benedetti Panici (Case Reports in Obstetrics and Gynecology)
Myomectomy is rarely performed during an ongoing pregnancy because of fear of miscarriage and the risk of an uncontrolled haemorrhage necessitating a hysterectomy. In cases where myomectomy is undertaken, most are performed at the time of cesarean section or with a laparoscopic approach. We report a case of a successful laparotomic myomectomy in the 16th week of pregnancy. A 35-year-old primigravida was admitted to our department with acute abdominal pain and hydronephrosis (serum creatinine 1.6 mg/dL). Imaging revealed a large implant myoma compressing the bladder, ureters, rectus, and gestational chamber and causing hydronephrosis. Laparotomic myomectomy was successfully performed and pregnancy continued uneventfully until the 38th week when a cesarean section was performed. Surgical management of myomas during pregnancy is worth evaluating in well-selected and highly symptomatic cases.